2017
DOI: 10.5114/aoms.2016.60091
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of microRNA-182 and microRNA-183 predicts progression of osteosarcoma

Abstract: IntroductionThe aim of this study was to investigate the expression levels of microRNA-182 and microRNA-183 and their association with clinicopathological features in patients with osteosarcoma.Material and methodsTotal RNA was purified from samples and noncancerous bone tissues and then quantitative real-time polymerase chain reaction was applied to evaluate the expression levels of microRNAs, and their relationship with clinicopathological features and survival in osteosarcoma patients.ResultsOur findings sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…non-coding RNAs (lncRNAs) are frequently deregulated and have critical roles in multiple cancers [4][5][6][7][8][9][10]. These non-coding RNAs could be novel candidates for prognostic biomarkers and therapeutic targets in various cancers including cervical cancer [9][10][11][12][13]. LncRNAs are a class of novel non-coding transcripts with more than 200 nucleotides in length [14,15].…”
mentioning
confidence: 99%
“…non-coding RNAs (lncRNAs) are frequently deregulated and have critical roles in multiple cancers [4][5][6][7][8][9][10]. These non-coding RNAs could be novel candidates for prognostic biomarkers and therapeutic targets in various cancers including cervical cancer [9][10][11][12][13]. LncRNAs are a class of novel non-coding transcripts with more than 200 nucleotides in length [14,15].…”
mentioning
confidence: 99%
“…The results in PCa are supported by studies in breast, lung, and bone cancers in which low expression of miR-182 has been associated with metastasis. 48 , 49 , 50 Conversely, studies in PCa cell lines have found high miR-182 as increasing in vitro and in vivo phenotypes of aggressiveness. 17 , 18 , 20 , 21 Measurement of miR-182 by RT-qPCR in prostate tumor specimens, not microdissected, have found either no significant association 21 , 47 or a positive association of miR-182 expression with recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA is a class of small molecule RNA that does not have the ability to encode protein. Micro-RNA has complex physiological functions and participates in the genesis of a variety of complex diseases, including cancers [3][4][5]. MiR-130b was up-regulated and acted as an oncogene in some kinds of cancers [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%